Proceedings of the 2006 International Workshop on Software Engineering for Automotive Systems 2006
DOI: 10.1145/1138474.1138485
|View full text |Cite
|
Sign up to set email alerts
|

Assessing merge potential of existing engine control systems into a product line

Abstract: Engine Control Systems (ECS) for automobiles have many variants for many manufactures and several markets. To improve their development efficiency, exploiting ECS commonalities and predicting their variability are mandatory. The concept of software product line engineering meets this ECS business background. However, we should carefully investigate the expected technical, economical, and organizational effects of introducing the strategy into existing products. Thereafter, a strategy will be derived systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This section discusses studies P71 [43], P94 [48], P173 [51], and P660 [74], which were found addressing the cost/effort estimation category. A number of studies consider the cost/effort estimation a key activity, especially in the course of planning a product line development endeavor.…”
Section: Cost/effort Estimationmentioning
confidence: 99%
See 3 more Smart Citations
“…This section discusses studies P71 [43], P94 [48], P173 [51], and P660 [74], which were found addressing the cost/effort estimation category. A number of studies consider the cost/effort estimation a key activity, especially in the course of planning a product line development endeavor.…”
Section: Cost/effort Estimationmentioning
confidence: 99%
“…Yoshimura et al [48,51] address effort estimation methods with two studies: the approach proposed in [48] describes a software clone analysis approach, and the approach discussed in [51] proposes an estimation process based on the return on investment (ROI). Both approaches are integrated into a process for merge potential assessment of existing variants, i.e., how to (economically) reintegrate variants back into the product line.…”
Section: Cost/effort Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we have introduced our experiences in analyzing and assessing systems implemented by the mechanisms of Cloning and Conditional Compilation, and our corresponding tools are Variant Analysis [14] and VITAL [46] respectively. In both these areas, there exist several other approaches and analysis tools, such as those developed for Cloning by Yoshimura et al [43], Mende et al [29] or Rubin et al [38], and those developed for Conditional Compilation by Kästner et al [23] or by Sincero et al [40]. However, the comparison of these approaches is beyond the scope of this paper.…”
Section: Related Workmentioning
confidence: 99%